The gene illusion : genetic research in psychiatry and psychology under the microscope - Joseph, Jay (Algora Pub., 2004)
Genetic factors are increasingly presented as an important influence on psychiatric disorders, personality, intelligence and various types of socially unacceptable behavior -- as if that were an unassailable fact, proven by research. Jay Joseph's timely, challenging book provides a much-needed rebuttal of the evidence cited in support of genetic theories in psychiatry and psychology, which are based mainly on twin and adoption studies. He shows that, far from establishing the importance of genes, psychiatric genetic and behavior genetic research on twins and adoptees has been plagued by researcher bias, unsound methodology and a reliance on erroneous theoretical assumptions. Furthermore, he discusses how this faulty research has been used to support the interests of those attempting to bolster conservative social and political agendas.